INNOVATION OF SUBJECT TECHNICAL GRAPHICS - DOSTAL, Jiri (Trends in education, 2010)
This paper presents the partial results of the project CZ.1.07/2.2.00/07.0002 "Modernisation of education: technology and informatics". This project is co-financed by the European social fund EU and the state budget of the Czech Republic.
Keywords: education; technology education; innovation.